Impact of Alcohol Consumption Among Teenagers in Moyag Todulan Village, Kotamobagu Timur Subdistrict, Kotamobagu City Bachelor's - Faradina Mokodongan; Sastro M. Wantu; Nopiana Mozin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aimed to determine the impact of alcoholic beverage (liquor) consumption among teenagers and to identify both preventive and repressive efforts in addressing such behavior in Moyag Todulan Village, Kotamobagu Timur Subdistrict, Kotamobagu City. The phenomenon of alcohol consumption among teenagers shows a worrying trend, marked by an increase in juvenile delinquency, fights, and social disturbances that concern the community. This research used a qualitative approach with a phenomenological method and data collection techniques including interviews, observation, and documentation. The results of the study indicate that alcohol consumption leads to various negative effects such as physical health issues, dependency, declining academic performance, and even law violations. Contributing factors include social environmental influences, lack of parental supervision, and low awareness among teenagers regarding the dangers of alcohol. Mitigation efforts are carried out through preventive measures like public awareness campaigns and repressive actions such as law enforcement and rehabilitation programs. This research recommends the active involvement of all elements, including parents, schools, and the government, in creating an environment free from the negative influence of alcohol to ensure a better future for the youth.